DESIGNING A SHORT FILM “FOOD HUNTERS” AS ONE OF MEDIA PROMOTION PALEMBANG CULINARY TOURISM - Fadhilah Khairani; Kuntum Trilestari (HOLISTICS, 2019)
In Palembang, there are few people promoting culinary through the film as promotion media. Whereas culinary in Palembang is very potential to be known by tourists. The purpose of this research was to know how to design a short film as one of media to promote Palembang Tourism Culinary. Through film as media, viewers can see repeatedly for a long period of time. So when they come to Palembang, they will remember the foods in the film and start trying them.  The writers used Research and Development method to conduct this research. To collect the data, the writers used interview and observation techniques and analyzed the data through validation instrument done by experts. The result of this research was film could be used as one of media to promote culinary tourism in Palembang. Moreover, the short film was uploaded to YouTube in order to see the responses from people or viewers of Palembang Culinary.